Targeting Personal Recovery of People With Complex Mental Health Needs: The Development of a Psychosocial Intervention Through User-Centered Design - van der Meer, Lisette; Jonker, Tessa; Wadman, Heleen; Wunderink, Charlotte; van Weeghel, Jaap; Pijnenborg, Gerdina Hendrika Maria; van Setten, Ellie R. H. (Frontiers in Psychiatry, 2021)
Long-term admissions in psychiatric facilities often result in a gradual erosion of the identity of people diagnosed with severe mental illnesses (SMI) into merely “patient”. Moreover, experiences of loss often reduced peoples' sense of purpose. Though regaining a multidimensional identity and a sense of purpose are essential for personal recovery, few interventions specifically address this, while at the same time take peoples' often considerable cognitive and communicative disabilities into consideration. This study describes the development process of a new intervention through user-centered design (UCD). UCD is an iterative process in which a product (in this case an intervention) is developed in close cooperation with future users, such that the final product matches their needs. The design process included three phases: an analysis, design, and evaluation phase. In the analysis phase, the 'problem' was defined, users’ needs were identified and design criteria were established. In the design phase, the collected information served as input to create a testable prototype using a process of design and re-design, in close collaboration with service users and other stakeholders. This resulted in an intervention entitled "This is Me" (TiM) in which service-users, together with a self-chosen teammate, actively engage in new experiences on which they are prompted to reflect. Finally, in the evaluation phase, TiM was implemented and evaluated in a real-life setting. In a small feasibility pilot, we found indications that some people indeed demonstrated increased reflection on their identity during the intervention. Furthermore, TiM seemed to benefit the relationship between the service users and the mental health professionals with whom they underwent the experiences. The pilot also revealed some aspects of the (implementation of) TiM that can be improved. Overall, we conclude that UCD is a useful method for the development of a new psychosocial intervention. The method additionally increased our knowledge about necessary factors in targeting personal recovery for people with complex mental health needs. Moreover, we conclude that TiM is a promising tool for supporting people with SMI in redeveloping a multidimensional identity and a renewed sense of purpose.